The psychological time as a tool of torture in the tale “The pit and the pendulum” by Edgar Allan Poe - Rocha, Jonas Eduardo (Revista de Letras, 2017)
The present article aims to analyse the way Edgar Allan Poe, through the construction of psychological time, creates the effect of suspense and terror characteristic of torture. For this, a survey on the Spanish Inquisition was conducted, based on authors such as Kamen (1966), in order to understand the period in which the story takes place in the tale “The Pit and the Pendulum.” Then a search on the gothic literature based on contributions from Rossi (2008) and stylistic features of Poe was made, followed by a study on the structural elements of the genre tale and the construction of narrative time, based on authors such as Todorov (1980), Gotlib (1995) and Moisés (1994). Finally, based on the studies cited, an analysis was made on how Poe used these elements - following the trend Gothic - to create in the reader the effect of psychological torture provided by the selected job.